1993
DOI: 10.2165/00003088-199324010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Fluconazole

Abstract: Fluconazole was recently developed for the treatment of superficial and systemic fungal infections. Triazole groups and insertion of 2 fluoride atoms increase the polarity and hydrosolubility of the drug, allowing it to be used in a parenteral form. Bioassay methods using Candida pseudotropicalis as a test organism were the first techniques used for the determination of fluconazole in body fluids. Gas chromatographic and high performance liquid chromatographic methods were later developed with better accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(176 citation statements)
references
References 74 publications
10
164
1
1
Order By: Relevance
“…The mean population pharmacokinetic parameter estimates were in the same range as those already reported [14,15,16,17]. Although a previous study reported no e ect of BW on¯uconazole pharmacokinetics [16], in this study BW signi®cantly in¯uenced¯uconaz-ole CL and V d .…”
Section: Discussionsupporting
confidence: 83%
“…The mean population pharmacokinetic parameter estimates were in the same range as those already reported [14,15,16,17]. Although a previous study reported no e ect of BW on¯uconazole pharmacokinetics [16], in this study BW signi®cantly in¯uenced¯uconaz-ole CL and V d .…”
Section: Discussionsupporting
confidence: 83%
“…However, interactions occur at the hepatic enzyme level where in vivo drug concentrations are unknown. In the particular case of azole compounds, tissue concentrations are sometimes higher than plasma concentrations [15,19]. Nevertheless, microsomal fractions are only an in vitro model and in vitro results must be extrapolated with caution with regard to the effect of drugs on ZDV glucuronidation in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Fluconazole is highly reabsorbed in the renal tubule. For drugs that are reabsorbed, PK Sim requires an input for the fraction of tubular reabsorption by calculating the glomerular filtration rate (GFR) fraction as follows: GFRFraction=EmpiricCLnormalRExpectedCLnormalRwhere Empiric CL R equals the renal plasma clearance reported in the literature 23. Expected CL R is the renal plasma clearance expected due to GFR if there was no reabsorption or tubular secretion (expected CL R  = fraction unbound × GFR =  f u  × 110 mL/minute).…”
Section: Methodsmentioning
confidence: 99%
“…Metabolism was attributed to glucuronidation via UGT2B7, and unbound intrinsic clearance (CLnormalI) was calculated using hepatic clearance (CL H ) 24. The CL H was assumed to be 15% of total empiric clearance 23. A summary of the assumptions used in the model building process is included in Table S1.…”
Section: Methodsmentioning
confidence: 99%